The Correlation Between Stress Level Perceived by Sixth-Semester Students of the English Education Study Program at UIN Raden Fatah and Their Speaking Mastery - Pernando, Taura; Jaya, Hariswan Putera (Journal of English Language and Education, 2026)
This study employed a quantitative correlational research design to explore the relationship between speaking proficiency and perceived academic stress among sixth-semester students of the English Education Study Program at UIN Raden Fatah University. The data were collected from 48 participants using the ETS Integrated Speaking Rubric to assess speaking proficiency and the Perceived Stress Scale (PSS10) to measure perceived academic stress. Descriptive statistical analysis revealed that most students experienced a moderate level of academic stress, while the majority of speaking mastery scores were classified in the “Good” category. Furthermore, Pearson Product Moment correlation analysis indicated that there was no statistically significant relationship between students’ perceived academic stress and their speaking proficiency. These findings suggest that speaking performance may not be directly influenced by general academic stress but is more closely related to factors such as speaking-specific anxiety, self-confidence, and language learning experience. Therefore, this study recommends that educators place greater emphasis on reducing language-specific anxiety rather than general academic stress to improve students’ speaking proficiency.